Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/pharmaceutics12030236
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Preferences and Willingness to Pay for Solid Forms of Oral Medications—Results of the Discrete Choice Experiment in Polish Outpatients

Abstract: Purpose: Personal preferences play an important role in the patients' decision process whether to adhere to treatment, or not. The purpose of this study is to assess Polish outpatients' preferences for solid forms of oral medications across various scenarios. Methods: The convenience sample of 200 outpatients took part in this study. According to the discrete choice experiment (DCE) design, participants were provided with selection of tablets and capsules, in different shapes, sizes, colors, and copayment leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…These tablets are difficult to feel in the mouth and can therefore lead to the perception they have not been completely swallowed, highlighting the importance of mouthfeel when optimising swallowability. Similar findings were reported in a study investigating patients’ willingness to pay for oral solid dosage forms; older patients were less negative about larger-sized tablets, partly due to the difficulties seeing and swallowing smaller-sized pills [ 35 ]. Difficulties swallowing as a result of tablets being “too small to sense” have also been reported within the general adult population [ 36 ].…”
Section: Discussionsupporting
confidence: 83%
“…These tablets are difficult to feel in the mouth and can therefore lead to the perception they have not been completely swallowed, highlighting the importance of mouthfeel when optimising swallowability. Similar findings were reported in a study investigating patients’ willingness to pay for oral solid dosage forms; older patients were less negative about larger-sized tablets, partly due to the difficulties seeing and swallowing smaller-sized pills [ 35 ]. Difficulties swallowing as a result of tablets being “too small to sense” have also been reported within the general adult population [ 36 ].…”
Section: Discussionsupporting
confidence: 83%
“…Recent study in Polish outpatients found out that patient priorities regarding various attributes of oral solid drug forms vary significantly between short-term and long-term treatments, and patients are happy to pay significantly more for drugs of their preferred characteristics (Kurczewska-michalak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This collection of attributes highlights the relevance of a multivariate approach to investigate and objectively demonstrate the influence of a variety of such factors. Using a stated-preference method, a recent study revealed variations in adult outpatients’ preferences and willingness to pay regarding some physical attributes of SODFs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%